RESILIENSI PADA PERAWAT ONKOLOGI RUMAH SAKIT KANKER X YANG PERNAH MENGALAMI COMPASSION FATIGUE - Gantari, Regina Lintang Laras; Wibawa, Dhevy Setya (MANASA, 2024)
The continuous workload and emotional burden experienced by oncology nurses at Hospital X can lead to compassion fatigue as a side effect of their work. The impacts include demotivation, low quality of care, and even risks to patient safety. This study aimed to examine the resilience process from compassion fatigue experienced by oncology nurses using qualitative methods. The researcher conducted semi-structured interviews with three nurses with different lengths of experience as oncology nurses. The results of this study showed that all three participants had achieved resilient reintegration with different ways to process it. The emotional burden due to the holistic issues of patients and their families and the complexity of care were the primary factors contributing to compassion fatigue. The research findings can be used to design preventive and remedial efforts to improve nurses' emotional and psychosocial well-being.